1994
DOI: 10.1001/archpsyc.1994.03950060020002
|View full text |Cite
|
Sign up to set email alerts
|

Independent Diagnoses of Adoptees and Relatives As Defined by DSM-III in the Provincial and National Samples of the Danish Adoption Study of Schizophrenia

Abstract: In the Provincial sample, the prevalence of "spectrum" disorders was significantly greater in biological relatives of schizophrenia spectrum vs control adoptees. The results were also consistent with the genetic transmission of individual diagnoses within the spectrum. When combined into the National sample, the results provided strong evidence for (1) the genetic transmission of DSM-III schizophrenia; (2) a genetic relationship between DSM-III schizophrenia, mainly schizophrenic schizoaffective disorder, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
96
0
4

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(106 citation statements)
references
References 41 publications
6
96
0
4
Order By: Relevance
“…The presence of thalamic shape abnormalities in the siblings of schizophrenia probands suggests that genetic influences contribute to their development because twin and adoption studies have indicated that shared environmental factors have a negligible contribution to the overall etiology of schizophrenia (Kendler et al, 1994;Cannon et al, 1998;Cardno et al, 1999). However, shared environmental factors could nonetheless have a nonnegligible contribution to abnormalities observed within particular cerebral structures.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of thalamic shape abnormalities in the siblings of schizophrenia probands suggests that genetic influences contribute to their development because twin and adoption studies have indicated that shared environmental factors have a negligible contribution to the overall etiology of schizophrenia (Kendler et al, 1994;Cannon et al, 1998;Cardno et al, 1999). However, shared environmental factors could nonetheless have a nonnegligible contribution to abnormalities observed within particular cerebral structures.…”
Section: Discussionmentioning
confidence: 99%
“…The study of schizotypy is of increasing interest to schizophrenia researchers given evidence that schizotypy and schizotypal personality disorder (SPD) relate phenotypically (Catts et al, 2000;Kendler et al, 1994;Siever et al, 1993) and genetically (Clementz et al, 1991;Kendler et al, 1995, Silverman et al, 1993 to schizophrenia. Ongoing research on schizotypy in non-clinical samples will deepen the field's understanding of this complex personality construct as a vulnerability marker, as an aspect of some cases of the schizophrenia prodrome, and as an indicator that can enhance genetic studies.…”
Section: Introductionmentioning
confidence: 99%
“…An example is the Danish Adoption Study of schizophrenia [8,9,10], which ascertained probands who had been adopted early in life and subsequently developed schizophrenia. 7.9% of first degree biological relatives of proband adoptees had DSM-III schizophrenia compared with 0.9% of first degree relatives of control adoptees [10].…”
Section: Adoption Studiesmentioning
confidence: 99%
“…7.9% of first degree biological relatives of proband adoptees had DSM-III schizophrenia compared with 0.9% of first degree relatives of control adoptees [10]. The Finnish Adoptive Study of Schizophrenia [11][12][13] took a different approach.…”
Section: Adoption Studiesmentioning
confidence: 99%